Pers Negara Bertetangga - Prajarto, Nunung (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 1998)
(Press Between Two Neighbouring Countries) Cultural differences between the Indonesian and Australian media sometimes create complaints and tensions. While the Australian media are generally regarded as being aggressive, fond of conflict, eager to get to the core of issues quickly and playing